Zur Taxonomie der Gattung Clypeocampulum GAULD (Hymenoptera, Ichneumonidae). - Schnee, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 2014)
The genus Clypeocampulum Gauld, 1976 is revised. The species name of the type species C. tibiale Gauld, 1976 is a new synonym of C. lubricum (Atanasov, 1975), comb. n. The validity of the genus is confirmed by new features. Clypeocampulum barbarae sp. n. from Spain and Clypeocampulum gauldi sp. n. from Turkey are described. A key enables the determination of the species. The distribution area of C. lubricum reaches from East Mediterranean countries to Central Asia. Some species of Pieridae (Lepidoptera) are recorded as hosts of C. barbarae and C. lubricum.KeywordsIchneumonidae, Anomaloninae, Clypeocampulum, new species, Pieridae as hosts.Nomenclatural Actsbarbarae Schnee, 2014 (Clypeocampulum), spec. n.gauldi Schnee, 2014 (Clypeocampulum), spec. n.lubricum (Atanasov, 1975) (Clypeocampulum), comb. n. hitherto Erigorgus lubricus Atanasov, 1975tibiale Gauld, 1976 (Clypeocampulum), syn. n. of Clypeocampulum lubricum (Atanasov, 1975)